Rebuilding: Organizing and Operating Under New Management. Issue 1 (18th May 2016) - Aladebumoye, Shade; Ellero, Nadine P.; Day, Annette
Abstract : In 2014, the highly experienced Head of Electronic Resources and Serials Services at Auburn University Libraries retired. Parallel changes in workflows, staffing, and organizational structure were also taking place, resulting in an intense period of transition that included merging two units. This presentation describes the transition process from the perspective of the new Head of Technical Services and one paraprofessional staff in the merged units. The presentation focuses on the processes of change, guiding philosophies, and lessons learned.